Surgical Clipping of Previously Coiled Recurrent Intracranial Aneurysms: A Single-Center Experience - Zheng, Yongtao; Zheng, Lili; Sun, Yuhao; Lin, Dong; Wang, Baofeng; Sun, Qingfang; Bian, Liuguan (Frontiers in Neurology, 2021)
Objective: This study reviews our experiences in surgical clipping of previously coiled aneurysms, emphasizing on recurrence mechanism of intracranial aneurysms (IAs) and surgical techniques for different types of recurrent IAs. Method: We performed a retrospective study on 12 patients who underwent surgical clipping of aneurysms following endovascular treatment between January 2010 and October 2020. The indications for surgery, surgical techniques and clinical outcomes were analyzed. Result: Twelve patients with previously coiled IAs were treated with clipping in this study, including 9 females and 3 males. The reason of patients with clipping were as follow: early surgery (Treatment fail in 2 patients, postoperative early rebleeding in 1 patient and intraprocedural aneurysm rupture during embolization in 1 patient); late surgery (aneurysm recurrence in 5 patients, SAH in 1, mass effect in 1 and aneurysm regrowth in 1). All aneurysms were clipped directly, and coil removal was performed in 4 patients. One patients died (surgical mortality, 8.3%), 1 patient (8.3%) experienced permanent neurological morbidity, and the remaining 10 patients (83.4%) had good outcomes. Based on our clinical data and previous studies, we classified the recurrence mechanism of IAs into coils compaction, regrowth, coils migration and coils loose. Then, we elaborated the specific surgical planning and timing of surgery depending on the recurrence type of IAs. Conclusion: Our experience indicates clipping is feasible in treating recurrent coiled IAs, although technical challenges are encountered. Our classification of recurrent coiled aneurysms into four types helps to assess the optimal surgical approach and the associated risks in managing them.